Osteoporosis Knowledge of Students in Relevant Healthcare Academic Programs. (19th November 2012) - Nguyen, Vu H.; Wang, Ze
Abstract : For healthcare professionals who treat individuals with osteoporosis, it is vital that they receive adequate education on osteoporosis to ensure sufficient knowledge of osteoporosis to properly treat individuals with the disease. To test for adequate osteoporosis education, a study was conducted to measure osteoporosis knowledge in 206 students in relevant healthcare academic programs, such as nursing, pharmacy, physical therapy, and dietetics. The study showed that differences existed in osteoporosis knowledge in general between the programs and between different years of students in the same programs. There were also discrepancies in specific areas of osteoporosis knowledge between the classes of students, and the average scores of correctly answered items were only as high as 24.40 (76.3%) out of 32 items on osteoporosis knowledge. This study shows that students have osteoporosis knowledge and that it is not completely inadequate; however, osteoporosis knowledge could still be more sufficient, and results demonstrate the need to increase osteoporosis education in the curriculum for these healthcare academic programs to increase osteoporosis knowledge and better prepare graduates and professionals to treat individuals with the disease.